A abelha melífera africanizada (Apis mellifera L.) na polinização e produção de óleo das sementes do pinhão manso (Jatropha curcas L.) - Rizzardo, Rômulo Augusto Guedes (2012)
The purpose of this thesis was to investigate the feasibility of using the honey bee (Apis mellifera L.) for pollination and yield increment in Jatropha curcas L. crops. Therefore, the floral biology and pollination process of J. curcas were studied as well as the foraging behavior and pollination efficiency of A. mellifera in this crop by the introduction of four colonies in a hectare. The work was carried out in a five years-old commercial plantation comprising 10ha, in the state of Piauí, (08°32’19,0”S and 43°56’19,7”W, 220 meters above sea level), Brazil, from March to July, 2009. Flowers were presented in protogynous inflorescences and the anthesis and most of pollen presentation took place mainly in the morning shift. Inflorescences last, in average, 20 days, with female flowers concentrating in the first third of the period and male flowers predominating in the second third, in a relation of 18.1:1 male/ female flower. Although this may favor xenogamy, the stigma receptivity lasts for, at least, five days ensuring the flower to reach the period of most pollen release in its own inflorescence, facilitating the occurrence of geitonogamy. Flowers pollinated up to four days after anthesis did not differ (p>0.05) in fruit setting to those pollinated in the first, second or third day after anthesis. Foraging by A. mellifera occurs throughout the day and peaks between 13h00min and 15h00min and is characteristic of nectar harvesting both in male and female flowers. Only one visit by A. mellifera to J. curcas flowers set 100% producing results similar (p>0,05) to those from manual xenogamy (96%), manual geitonogamy (94%) and open pollination (93%). However, only one visit by a bee was not enough to maximize the oil content per seed (213mg) in comparison to the open pollination and geitonogamy treatments (both 250mg). Besides that, it was possible to observe that geitonogamy led to greater oil production than xenogamy (237mg). It is concluded that A. mellifera is an efficient pollinator of this crop. The introduction of four honey bee colonies per hectare maximize oil production and produce the best results for all parameters studied. Furthermore, only one visit by the honey bee to J. curcas flowers was enough to prevent pollination deficit in this crop.